BUDAYA LONGKO' TORAJA DALAM PERSPEKTIF ETIKA LAWRENCE KOHLBERG - Pasande, Diks Sasmanto (Jurnal Filsafat "WISDOM", 2013)
This research studies one of the local wisdoms in Toraja society which is longko' or culture of shame. This culture contains values of religious ethics and communal spirit to maintain self-esteem and vigilance in order to be not humiliated/ shamed (kalongkoran). The longko' of Toraja is observed from the ethics perspective of Lawrence Kohlberg to analyze ethical values of the culture. The result of this research indicates that, according to the Kohlberg's theory of moral development stages, Toraja society tends to be at the conventional level and the third stages which is characterized by a social morality where the union with familiar groups becomes the highest value. It is in accordance with communal ties which are very strong in the Toraja society and known as tongkonan. The longko', as an internalization result of understanding varieties which is held steadfastly by the Toraja society, contains not only values of honor, self esteem and shame, but also other positive values such as work ethos and spirit. Kamalamburan (honesty) and karapasan (harmony and peace) are the main values of Toraja society. The Longko' is quite relevant, especially in relation to the national efforts to solve the problem of corruption through the cultural approach.